2018
DOI: 10.2147/cmar.s157506
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram for the prediction of intrahepatic cholangiocarcinoma in patients with intrahepatic lithiasis complicated by imagiologically diagnosed mass

Abstract: BackgroundAccurate preoperative diagnosis of intrahepatic cholangiocarcinoma (ICC) among patients with imagiologically intrahepatic lithiasis (IHL) complicated by mass is crucial for timely and effective surgical intervention. The aim of the present study was to develop a nomogram to identify ICC associated with IHL (IHL-ICC).Patients and methodsData were obtained from a total of 252 consecutive patients with IHL complicated by mass. Multivariate logistic regression analysis was conducted to identify the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
12
2
Order By: Relevance
“…Nomograms have been widely used as a valuable pictorial tool for combining biological and clinical variables in the construction of prognostic models using traditional statistical methods such as a Cox proportionalhazards regression model to determine the prognosis of multiple malignancies [8][9][10]. In addition, several studies have shown that a nomogram is superior to the AJCC TNM staging system in predicting the survival of cancer patients [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms have been widely used as a valuable pictorial tool for combining biological and clinical variables in the construction of prognostic models using traditional statistical methods such as a Cox proportionalhazards regression model to determine the prognosis of multiple malignancies [8][9][10]. In addition, several studies have shown that a nomogram is superior to the AJCC TNM staging system in predicting the survival of cancer patients [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we had developed a nomogram to predict ICC for patients with IHL complicated by the presence of a imagologically diagnosed mass ( 17 ). However, the imagological diagnosis in the nomogram was made by radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…A radiomic model incorporating the radiomic signature, as well as independent risk factors that were obtained in our previous research for IHL-ICC ( 17 ), was constructed based on the results of the multivariate logistic regression analysis performed on the training cohort. A radiomic nomogram was then constructed in order to provide clinicians with a visual tool through the use of the selected covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Nomograms have been widely used as a valuable pictorial tool for combining biological and clinical variables in the construction of prognostic models using traditional statistical methods such as a Cox proportional-hazards regression model to determine the prognosis of multiple malignancies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%